Perspective and Spatial Illusion as Language and Technique in Urban Art of JR (diségno, 2025)
Street Art, as the set of artistic and performative practices within the urban space, represents one of the most significant artistic movements of modernity. Through visual imagery, Street Art invites viewers to reconsider the reality surrounding them, engaging them in a process of reinterpretation of the lived and traversed space. In this context, illusory representations, with their ability to alter perception through ephemeral spatial suggestions, offer fertile ground for experimentation by street artists. The artistic production of the Paris-based urban artist Jean René, widely known as JR, is emblematic in this regard. This study focuses on the exploration of trompe l’œil and anamorphosis as visual languages and techniques within JR’s artistic practice. The aim of the research is to analyze how figurative techniques of Renaissance origin are interpreted in his urban artworks, to make explicit the complex relationship between stylistic choices and the communicative purposes of the artistic project. Through an in-depth examination of selected works, the research intends to show how the perspective construction of illusory space, reinterpreted through photography and new media, is today a visual and symbolic language capable of conveying unprecedented visions and representations of contemporary urban space.
Keywords: street art; JR; illusory perspectives; trompe l’œil; anamorphosis